Experiences with the Falling Weight Deflectometer (FWD) Used for Construction Quality Control of the Different Pavement Layers - Bockelmann, Carol (2025)
Given the difficulty in securing budgets in Colombia, along with the lack of a maintenance-oriented culture among government agencies, it becomes imperative to execute road construction works with total quality. In order to achieve this total quality, it is essential, among other factors, to carry out thorough quality control at each stage of the pavement construction process.